Análisis de los factores de riesgo psicosociales en la empresa Oliojoya Industria Aceitera Cía. Ltda. en el año 2024. - Torres Cobos, Stalyn Marcelo (2026)
At Oliojoya Industria Aceitera Cía. Ltda., identifying and managing psychosocial risks is one of the main challenges facing the Health, Safety, and Environment department, given their direct impact on the overall well-being of workers. This research identified the psychosocial risk factors present in the organization through a structured survey based on the methodology of the National Institute for Occupational Safety and Health (INSST) and supplemented by the FPSICO 4.1 application assessment. The study adopted a descriptive-evaluative approach, with a non-experimental, cross-sectional design, allowing for analysis of the actual situation without manipulation of variables. The results showed that the factors with the highest incidence were: psychological demands (57.5%), participation and supervision (52.5%), and interest in the worker/compensation (70%). Likewise, it was identified that the areas with the highest level of exposure correspond to participation/supervision and workload, reaching very high risk levels of 100% in the departments of Fractioning, Cleaning; Yard-Tank, Warehouse, and Supplies; Logistics; Accounting; File Control; and Management Secretariat.. As an innovative contribution, a predictive model with a four-year projection was developed, aimed at anticipating the evolution of psychosocial risks and strengthening their prevention. This tool provides strategic support for the continuous improvement of the organizational climate and occupational health within the company.